Effects of the MILA in the efficiency of the colombian, peruvian, and chilean stock market portfolios - Uribe Gil, Jorge Mario; Mosquera López, Stephania (Cuadernos de Administración, 2014)
This work explored the effect in terms of portfolio efficiency (in means and variance) of the implementation of the Latin American Integrated Market (MILA, for the term in Spanish). The analysis was based on the construction of a Sharpe ratio with monthly frequency, with daily data, for the stock indexes from the three countries involved (Chile, Peru, and Colombia), with special emphasis on the results found for the Colombian market. It was found that the agreement has yet to produce a structural change in the series that measures the evolution of the stock market in Colombia, which during the study period has only presented a endogenous structural break, associated to the change in posture in the monetary policy by the Bank of the Republic (Central Bank) for the first quarter of 2006. The Chilean and Peruvian stock markets did not show that the agreement produced a structural change in the series of the Sharpe ratios. The results found for the three countries may be because the MILA is still an incipient market and because transaction volumes are low